Women war workers in engineering, 1940 (1940)
1940 1939-1945 "Women war workers in engineering, 1940" [T0239.jpg], 1940, The Times This press cutting from 'The Times' of 30 January 1940 reports the concerns of the Amalgamated Engineering Union regarding dilution and equal pay following from Winston Churchill's plans to introduce more women into the industry.